2002
DOI: 10.1159/000066137
|View full text |Cite
|
Sign up to set email alerts
|

Drugs in the Postsocialist Transitions of Estonia, Latvia, Lithuania and Poland

Abstract: The article discusses problems related to illicit drugs in Poland, Lithuania, Latvia and Estonia against the background of the postsocialist transitions of the 1990s. Besides the drug problem, the political and market reforms of the 1990s were accompanied by a surfacing of a variety of social problems, some of which had already been present during the authoritarian socialist regimes. Gaining reliable and comparable statistics on drug-related harm has become very difficult due to changes in treatment system and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…In Eastern Europe, drug use was not unknown during the socialist era, (Lagerspetz & Moskalewicz, 2002) and was labeled as a moral problem, stigmatized and criminalized. Injection drug use epidemics emerged in the 1990s and have led to some of the highest HCV prevalence rates among PWID (Nelson, et al, 2011) reported in the world.…”
Section: Estoniamentioning
confidence: 99%
See 1 more Smart Citation
“…In Eastern Europe, drug use was not unknown during the socialist era, (Lagerspetz & Moskalewicz, 2002) and was labeled as a moral problem, stigmatized and criminalized. Injection drug use epidemics emerged in the 1990s and have led to some of the highest HCV prevalence rates among PWID (Nelson, et al, 2011) reported in the world.…”
Section: Estoniamentioning
confidence: 99%
“…(Lagerspetz & Moskalewicz, 2002) The transition from Soviet occupation to autonomy brought about major societal upheaval. Employment fell by one fifth, the gross domestic product decreased by nearly 40% (Lauristin & Pettai, 2011; Staehr, 2004) and there were cuts in social services linked to loans from international lenders.…”
Section: Estoniamentioning
confidence: 99%
“…opiates. In comparison with other regions of Estonia, the inhabitants of Narva use more heroin and home-made poppy liquid --the same substance reported in Poland since the 1970s as ''polski kompot'' (Lagerspetz and Moskalewicz 2002). This narcotic substance is prepared and used intravenously in the company of others and the intake often takes the form of a bonding ritual.…”
Section: Patterns Of Drug Usementioning
confidence: 94%
“…Similarly to other countries in Eastern and Central Europe, Estonia has a relatively brief experience of problems related to the use of illicit substances (Lagerspetz & Moskalewicz 2002). In the previously "Real Socialist" countries in general, the increase in drug use among youth (witnessed by Western countries since the 1970s) did not take place until the 1990s.…”
Section: Taking Control By Loosing Control? Introduetionmentioning
confidence: 99%